Crystal structure of the cocrystal 1,3,5,7-tetranitro-1,3,5,7-tetrazoctane ─ 2,3-dihydroindole (1/1), C12H17N9O8 - Liu Penghua; Xing Jiangtao; Wang Zhiqiang; Wang Baomin (Zeitschrift für Kristallographie - New Crystal Structures)
C12H17N9O8, orthorhombic, Pna21 (no. 33), a = 11.376(4) Å, b = 7.966(2) Å, c = 19.076(6) Å, V = 1728.6(9) Å3, Z = 4, Rgt(F) = 0.0373, wRref(F2) = 0.0908, T = 296 K.